2001
DOI: 10.1081/pln-100104978
|View full text |Cite
|
Sign up to set email alerts
|

ROOT AND SHOOT PERFORMANCE OF THREE CREEPING BENTGRASS CULTIVARS AS AFFECTED BY NITROGEN FERTILITY*

Abstract: Cultivar selection and nitrogen (N) fertility signi®cantly in¯u-ence the performance of creeping bentgrass (Agrostis palustris Huds.) in warmer regions of the United States. This study was conducted to determine the effects of N on root and shoot growth of three creeping bentgrass cultivars. The effect of three N rates (195.3, 390.6, and 586.0 kg Naha year) on the total root length density (TRLD), deep root length density (DRLD), visual shoot quality, shoot density, and root to shoot ratio (RSR) of Crenshaw',`… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 28 publications
5
19
0
Order By: Relevance
“…Our moderate N rate was similar to or low compared with rates used by other researchers. Schlossberg and Karnok (2001) found that shoot quality and shoot density of both Penncross and L‐93, mowed at 4 mm and well watered, improved as N rates increased from 195 to 390 to 586 kg ha −1 yr −1 on a sand‐based root zone. In Rhode Island, Boesch and Mitkowski (2007) studied SR7200 response to a range of N rates from 0 to 243 kg ha −1 N yr −1 and concluded that a minimum of 196 to 243 kg ha −1 N yr −1 was necessary for acceptable quality turf.…”
Section: Discussionmentioning
confidence: 97%
“…Our moderate N rate was similar to or low compared with rates used by other researchers. Schlossberg and Karnok (2001) found that shoot quality and shoot density of both Penncross and L‐93, mowed at 4 mm and well watered, improved as N rates increased from 195 to 390 to 586 kg ha −1 yr −1 on a sand‐based root zone. In Rhode Island, Boesch and Mitkowski (2007) studied SR7200 response to a range of N rates from 0 to 243 kg ha −1 N yr −1 and concluded that a minimum of 196 to 243 kg ha −1 N yr −1 was necessary for acceptable quality turf.…”
Section: Discussionmentioning
confidence: 97%
“…This is especially important for potassium as it has been found to have nonuniform distribution in grasses. [6] In a Reed canarygrass root development study conducted in Europe, [7] root mass of N-fertilized reed canarygrass increased for four years and then stabilized. As vegetative competition increased in mixed stands, reed canarygrass allocated more biomass to roots.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this difference was not apparent. The N demand of managed turfgrass is governed by species, temperature, light, and performance goals for the surface (Carrow et al, 2001; Schlossberg and Karnok, 2001; Kussow et al, 2012). In sod production for American football, where surface stability underfoot is a primary concern, moderating annual N rates to <244 kg N ha −1 may improve the surface stability of the sod at the time of installation.…”
Section: Discussionmentioning
confidence: 99%